2018
DOI: 10.1038/s41467-018-07368-7
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated genotypes of the commensal skin bacterium Staphylococcus epidermidis

Abstract: Some of the most common infectious diseases are caused by bacteria that naturally colonise humans asymptomatically. Combating these opportunistic pathogens requires an understanding of the traits that differentiate infecting strains from harmless relatives. Staphylococcus epidermidis is carried asymptomatically on the skin and mucous membranes of virtually all humans but is a major cause of nosocomial infection associated with invasive procedures. Here we address the underlying evolutionary mechanisms of oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(158 citation statements)
references
References 76 publications
(106 reference statements)
12
144
0
2
Order By: Relevance
“…In the phylogenetic trees reported, pathogenic SE strains are intermingled with commensal SE strains with no pathogenic cluster found (Meric et al 2018;Miragaia et al 2005). Recently, Meric et al suggested, that pathogenic SE subpopulations occur within the commensal SE strains, which contain genes and alleles necessary for colonization at distinct infection sites (Meric et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the phylogenetic trees reported, pathogenic SE strains are intermingled with commensal SE strains with no pathogenic cluster found (Meric et al 2018;Miragaia et al 2005). Recently, Meric et al suggested, that pathogenic SE subpopulations occur within the commensal SE strains, which contain genes and alleles necessary for colonization at distinct infection sites (Meric et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic basis for pathogenicity of SE strains includes genes related to biofilm formation (adhesion), phenol soluble modulins (PSMs), and diverse Mobile Genetic Elements (MGEs) like phages, insertion sequences (ISs), and pathogenicity islands, that may be associated with the transfer of antibiotic and virulence traits (Bouchami et al 2016;Miragaia et al 2009;Rolo et al 2017) (Conlan et al 2012;Kozitskaya et al 2005;Meric et al 2015). There is no clear genetic distinction between pathogenic and commensal non-pathogenic SE strains, even though nosocomial strains are enriched in virulence and antibiotic resistance genes (Conlan et al 2012;Kozitskaya et al 2005;Meric et al 2018). It has been proposed that these genes are within the pool of accessory genome mobilized within and between species (Meric et al 2015;Rolo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Staphylococcus epidermidis, a commensal inhabitant of human skin and mucous membranes, has emerged as a relevant opportunistic pathogen in hospitals. This opportunistic pathogen causes infections, mainly in the elderly and immunocompromised individuals [32,33]. Wound The exposed subcutaneous tissue, devitalized tissue (ischemic, hypoxic, or necrotic), and the compromised immune system of the host provide optimal conditions for microbial colonization and growth [31].…”
Section: Microorganisms Present In Chronic Woundsmentioning
confidence: 99%
“…For instance, Staphylococcus epidermidis, a commensal inhabitant of human skin and mucous membranes, has emerged as a relevant opportunistic pathogen in hospitals. This opportunistic pathogen causes infections, mainly in the elderly and immunocompromised individuals [32,33]. Wound contamination can also occur through cross-infection events, such as poor hand hygiene practiced by healthcare clinicians after wound cleansing and dressing procedures, coughing and sneezing, dirty bedding, unsterilized medical equipment, and prolonged use of catheters, tubes, or intravenous lines [34][35][36][37][38].…”
Section: Microorganisms Present In Chronic Woundsmentioning
confidence: 99%
“…In the clinical microbiology laboratory, machine learning algorithms developed from population genomics could be used to predict infection risks from the genomic features of Staphylococcus epidermidis and potentially identify highrisk genotypes preoperatively to target pre and postoperative HAI preventative programs [18]. AI-enhanced laboratory microscopy could streamline the rapid diagnosis of patients with infection and assist AMR prevention programs by facilitating targeted antimicrobial management and IPC intervention.…”
Section: Diagnosis Of Infection With Ipc Implicationmentioning
confidence: 99%